Pemanfaatan Aplikasi E-Government dalam Meningkatkan Efektivitas Pelayanan Publik di Pemerintahan Daerah (Studi Kasus pada Pemerintah Kabupaten Sleman) - Ihcsan, Muhammad; Fahlevvi, Mohammad Rezza; Buding, Asri (Edutik : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2025)
The development of information technology drives digital transformation in government governance, one of which is through the implementation of e-Government applications at the regional level. This research aims to analyze the utilization of e-Government applications in improving the effectiveness of public services within the Sleman Regency Government. The research employs a qualitative descriptive approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies of applications such as E-Lapor, SIMPADU, and SiJempol. The research results show that e-Government implementation has a significant impact on service speed, accessibility, information transparency, and community participation. For example, population administration services that previously required 3-5 days can now be completed within 1-2 days. Nevertheless, there are still obstacles in the form of low digital literacy among the community, limited ICT infrastructure in peripheral areas, and insufficient human resource capacity among government officials. Therefore, sustainable strategies are needed in the form of digital training, infrastructure improvement, and user data protection. These findings confirm that e-Government success does not only depend on technology, but also on institutional and social readiness of the community.